X men noir - Van Lente, Fred; Calero, Dennis (New York, NY Marvel Pub, 2009)
Homicide detectives investigate a murder that points to the involvement of Wolverine and brings attention to Xavier's school.
"Contains material originally published in magazine form as X-Men Noir #1-4"--T.p. verso.
Keywords: X-Men (Fictitious characters) -- Comic books, strips, etc; Police -- Comic books, strips, etc; Murder -- Investigation -- Comic books, strips, etc; Corruption -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Superheroes -- Comic books, strips, etc; Science fiction comic books, strips, etc